2020
DOI: 10.1055/s-0040-1713806
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Pessary Plus Progesterone for Twin Pregnancy with Short Cervix Compared to Unselected and Non-Treated Twin Pregnancy: A Historical Equivalence Cohort Study (EPM Twin Pessary Study)

Abstract: Objective The present study aims to determine if the use of cervical pessary plus progesterone in short-cervix (≤ 25 mm) dichorionic-diamniotic (DC-DA) twin pregnancies is equivalent to the rate of preterm births (PBs) with no intervention in unselected DC-DA twin pregnancies. Methods A historical cohort study was performed between 2010 and 2018, including a total of 57 pregnant women with DC-DA twin pregnancies. The women admitted from 2010 to 2012 (n = 32) received no treatment, and were not select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…The remaining 28 studies were retrieved for full-text review, of which 12 papers did not meet the inclusion criteria for the following reasons: although cervical pessary combined with progesterone treatment was applied in partial patients, these patients were not individually analyzed in four studies; only cervical pessary or progesterone alone treatment, not combined treatment was used in five studies; two studies were protocols; singleton and multiple pregnancies were not individually analyzed in one study. Sixteen studies, with 1517 participants in the cervical pessary and vaginal progesterone combined therapy group and 1600 women in the control group were finally included [ 8 12 , 17 27 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 28 studies were retrieved for full-text review, of which 12 papers did not meet the inclusion criteria for the following reasons: although cervical pessary combined with progesterone treatment was applied in partial patients, these patients were not individually analyzed in four studies; only cervical pessary or progesterone alone treatment, not combined treatment was used in five studies; two studies were protocols; singleton and multiple pregnancies were not individually analyzed in one study. Sixteen studies, with 1517 participants in the cervical pessary and vaginal progesterone combined therapy group and 1600 women in the control group were finally included [ 8 12 , 17 27 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The cervical length of patients was less than 25 mm in most of studies (15/16, 93.9%). Of 16 studies, 12 studies [ 8 , 10 12 , 18 – 22 , 25 27 ] involved women with a singleton pregnancy and the other four [ 9 , 17 , 24 , 27 ] included women with multiple pregnancies. Five RCT [ 10 12 , 19 , 25 ] and four non-RCT [ 18 , 21 , 26 , 27 ] singleton studies included a control group receiving treatment with vaginal progesterone alone; two non-RCT singleton studies compared with a group receiving the combination of cervical cerclage and vaginal progesterone [ 18 , 20 ]; only one non-RCT singleton study used the group receiving vaginal progesterone + cervical cerclage + cervical pessary [ 18 ], tocolysis (ritodrine hydrochloride and magnesium sulfate) [ 22 ] or cervical pessary alone [ 8 ] as the control, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One retrospective cohort study of twin pregnancies draws a conclusion that cervical pessary combined with vaginal progesterone could prolonged pregnancy and reduce risk of adverse neonatal outcomes [24]. In 2020, a retrospective study of 57 patients with (dichorionic diamniotic twin (DCDA) showed that a cervical pessary combined with vaginal progesterone reduced the rate of preterm birth in patients [25]. There is one study showed that cervical pessary combined with vaginal progesterone could prolonged pregnancy, reduce prematurity rate and a low rate of perinatal complications [26].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…26 There is some evidence that the use of CP in twin pregnancy with a short cervix may produce a similar outcome of low-risk twin gestation. 27…”
Section: Short Cervix In Twin Gestationmentioning
confidence: 99%